Analysis of Microplastics in Water and Biofilm Matrices in Metro River, East Java, Indonesia - Sari, Safitri Permata; Kartikaningsih, Hartati; Yanuar, Adi Tiya; Kurniawan, Andi (The Journal of Experimental Life Science, 2022)
The Metro River flows from upstream to downstream across East Java to support several human activities such as household, toilets, or agriculture. The utilization of water rivers must be balanced with water quality monitoring so that the quality of the water can be monitored. This study aims to analyze the abundance of microplastic in the Metro River. Moreover, the water parameters (pH, dissolved oxygen, temperature, flow velocity) were also measured. Sampling was carried out at three different stations, namely station 1 representing the agricultural activity area, station 2 representing the household activity area, and station 3 representing industrial activity. This study shows the abundance of microplastics in biofilm matrices and surrounding river water. The types of the microplastics are fibers, fragments, and films. The total abundances of microplastics in river water ranged from 0.8 - 1.61 particle.mL-1, while the biofilm matrices ranged from 7.4 to 9.5 particle.gram-1. The results of water quality parameters at all stations are still relatively good compared to quality standards. To the best of our knowledge, this study was the first study that reports the microplastics in the water of and inside biofilm formed on Metro River.